The first election of the President of the United States and Europe: historical and legal aspects. (Journal of actual problems of jurisprudence, 2016)
The election of the Head of State of the Republic of Kazakhstan remain relevant. Investigation Institute of election of the President of the Republic of Kazakhstan can not be carried out without taking into account international experience in the development of the electoral law governing the procedure for electing the President. Only by examining the particular history of presidential elections in the developed countries, identifying the main trends of its development, it is possible to understand and to offer the best legal reforms in this area.
Keywords: president; elections; human rights; the state independence